KUALITAS PELAYANAN PERIZINAN DAN NON PERIZINAN MELALUI APLIKASI SICANTIK CLOUD DI KABUPATEN TEBO JAMBI - Nazila; Ayuninsih, Eva; Hapsa; Fatriani, Riri Maria (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to analyze the quality of licensing and non-licensing services through the SICANTIK Cloud application at DPMPTSPKUKM Tebo Regency. The research method uses a descriptive qualitative approach by referring to the Zeithml, Parasuraman & Barry service theory which includes five dimensions: physical evidence, reliability, responsiveness, assurance, and empathy. The results showed that the implementation of the SICANTIK Cloud application as a breakthrough to simplify the licensing process has gone well, but the dimensions of physical evidence and reliability are still not optimal in facilitating community service, while the dimensions of responsiveness, assurance, and empathy have shown good performance even though they have not reached the maximum level.